The medieval French Alexander - Maddox, Donald; Sturm-Maddox, Sara. (Albany : State University of New York Press, 2002)
"Alexander the Great was one of the legendary Nine Worthies in the medieval canon of ancient and modern heroes, and medieval writers exploited his legend in a wide variety of literary and didactic texts. Addressing the classical legacy to the Middle Ages as expressed in four centuries of vernacular narratives, this volume offers the first systematic collective study of Alexander the Great's thematic prominence in medieval culture. Contributors from Britain, France, the Netherlands, and the United States combine sensitive textual analyses with perspectives from such diverse fields as art history, codicology, anthropology, sociology, the history of mentalities, and postcolonial theory. Overall, the collection offers a provocative rethinking of the monumental medieval French tradition of Alexander the Great, as well as valuable insight into the emergence and transformations of French literature between the early twelfth century and the end of the Middle Ages."--Jacket
The prologue to the Historia de preliis: a pagan model of spiritual struggle / Michel Zink -- The raid on Gaza in Alexandre de Paris's romance / Emmanuèle Baumgartner -- Alexander's Clergie / Douglas Kelly -- Alexander and Aristotle in the French Alexander Romances / Catherine Gaullier-Bougassas -- Alexander's Gabs / Franc̦ois Suard -- "Mout est proz e vassaus"/"Mout es corteis": Vasselage and courtesy in the Roman d'Alexandre / Rupert T. Pickens -- "A paine a on bon arbre de malvaise raïs": counsel for kings in the Roman d'Alexandre / William W. Kibler -- Giving fiefs and honor: largesse, avarice, and the problem of "feudalism" in Alexander's testament / Stephen D. White -- Take the world by prose: modes of possession in the Roman d'Alexandre / Michelle R. Warren -- Alexander and Caesar in the Faits des romains / Catherine Croizy-Naquet -- Alexander the Great as the icon of perfection in the epigones of the Roman d'Alexandre (1250-1450): the Utilitas of the ideal prince / Martin Gosman -- Ekphrasis and memory in the fourteenth-century Parfait du paon / Renate Blumenfeld-Kosinski -- Conquering Alexander: Perceforest and the Alexandrian tradition / Michelle Szkilnik -- Alexander amoroso: rethinking Alexander in the Roman de Perceforest / Jane H.M. Taylor -- From Alexander to Marco Polo, from text to image: the marvels of India / Laurence Harf-Lancner -- "Codices manuscriptos nudos tenemus": Alexander and the new codicology / Keith Busby.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Romances -- History and criticism; Alexandre, -- le Grand, -- 356-323 av. J.-C -- Romans, nouvelles, etc. -- Histoire et critique; Alexander, -- the Great, -- 356 B.C.-323 B.C.; French literature -- To 1500 -- History and criticism; Littérature française -- Jusqu'à 1500 -- Histoire et critique; LITERARY CRITICISM -- European -- French; French literature; Romances; Alexanderliteratuur; Bellettrie; Frans; To 1500; Criticism, interpretation, etc